Terrorism and Africa: on the danger of further attacks in Sub-Saharan Africa - Mair, Stefan (2003)
Abstract: "The attacks in Mombasa of November 2002 have drawn attention to a region of the world that had been considered a minor stage in the fight against terrorism following September 11, namely sub-Saharan Africa. The alliance against terrorism previously limited its efforts in this area to preventing al-Qaida fighters from finding refuge in the Horn of Africa. What seemed to have been forgotten was that the first monstrous attacks by al-Qaida took place in East Africa. In 1998, the US embassies in Nairobi and Dar es Salaam were bombed, killing 291 and 10 people respectively. The recent actions of al-Qaida in the region raise two questions: Does Africa threaten to become a hotspot of international terrorism? And, how can terrorist attacks in Africa be prevented in the future?" (author's abstract)